The impact of ellagic acid on some apoptotic gene expressions: a new perspective for the regulation of pancreatic Nrf-2/NF-?B and Akt/VEGF signaling in CCl4-induced pancreas damage in rats - Aslan, Abdullah; Beyaz, Seda; Gok, Ozlem; Can, Muhammed Ismail; Erman, Fazilet; Erman, Orhan (Taylor & Francis Ltd, 2021)
Objective: The aim of this study was to evaluate the potential effect of ellagic acid (EA) in the treatment of pancreatic injury. EA has been found to have strong anti-inflammatory, antioxidative, and anticancer properties. The effects of EA on pancreatic star cell (PSC) activation and cell functions have been evaluated and it has been shown that it inhibits the activation of basic cell functions and PSCs and(.) it has antidiabetic activity through its effect on beta-pancreas cells. Materials and methods: In this work, 36 Wistar albino rats (n = 36, 8 weeks old) were used. Rats were divided to 4 groups and 9 rats were each group. Groups: Group 1: control group; Group 2: EA group; Group 3: carbon tetrachloride (CCl4) group; Group 4: EA + CCl4 group. Animals were decapitated after 8 weeks and their pancreas tissue samples were taken and researched. In pancreas tissue, NF-kappa B, TNF-alpha, Nrf-2, VEGF, Bcl-2, caspase-3, and Akt proteins expression ratios were analyzed by western blotting method, CAT activity and GSH levels were determined by spectrophotometer and ROS production was detected by MDA. Results: In our results, the Nrf-2 and caspase-3 protein expressions, catalase activities and GSH levels increased, TNF-alpha, NF-kappa B, Bcl-2, VEGF, and Akt protein expressions and MDA levels reduced in EA + CCl4 group comparable to the CCl4 group. Conclusions: These findings reveal that EA decreases pancreas tissue injury in rats and that EA may also be used as a drug against pancreas tissue injury in the future.
Keywords: Protein kinase B; B-cell lymphoma 2; ellagic acid; nuclear factor kappa B; pancreas damage